Commercialized Intercollegiate Athletics - Matthew J. Mitten; James L. Musselman; Bruce W. Burton (University of Kansas Libraries, 2009)
This article observes that American society's passion for intercollegiate sports competition is an extremely powerful, naturally evolved cultural force. The marketplace responds to cultural forces, and the commercialization of college sports directly reflects the marketplace realities of our society. For example, colleges and universities rationally use their intercollegiate athletic programs, particularly NCAA Division 1 FBS football and basketball, as a means to achieve a wide range of legitimate objectives of higher education. Thus, the authors advocate that university athletic department revenues should continue to be exempt from federal taxation, specifically the unrelated business income tax (UBIT), despite the increasingly commercialized nature of intercollegiate sports. However, the commercialization of intercollegiate athletics creates the potential for conflict with a university's academic mission and the risk that student-athletes may be exploited. The authors propose that Congress provide the NCAA and its member universities with a limited exemption from the federal antitrust laws conditioned upon targeted reforms that will 1) ensure that intercollegiate athletics are primarily an educational endeavor; 2) better enable student-athletes in revenue-generating sports to obtain the benefit of their bargain; and 3) protect and maintain student-athletes' intercollegiate athletics participation opportunities in nonrevenue generating sports.